CULTIVATING KNOWLEDGE IN AI ERA: ESSENTIAL DIGITAL RESOURCES ANDTOOLS FOR AGRICULTURAL RESEARCHERS - N.P. RAVI KUMAR; M. SANDHYA (The Journal of Research, PJTSAU, 2026)
Agricultural research todayoperates within a digital knowledge environment that combines field experiments, remote sensing, genomics, socio-economic inquiry, scholarly literature, research data and collaborative networks. This article identifies the most significant digital resources available to agricultural researchers and presents them in an outline. It differentiates specialized discovery services such as CAB Abstracts, AGRICOLA, FAO AGRIS, and J-Gate Agricultural and Biological Sciences from multidisciplinary citation databases, including Google Scholar, while also elaborating on the complementary role of the One Nation One Subscription initiative. The article examines the pathways to open science through the ICAR Open Access Policy, KrishiKosh, DOAJ, Dryad, Zenodo, AgriRxiv, and bioRxiv.It further describes the effective use of reference managers, researcher identifiers, collaboration profiles, field-data applications, MOOCs, and more. Mastery of this ecosystem may shorten the time required to transform reliable information into resilient agricultural solutions. The article concludes that while artificial intelligence can enhance semantic discovery, screening, extraction, and data mining, researchers must retain control over the search process, logic, source verification, ethics, privacy, and understanding.